Illegitimate child inheritance: an analysis from syariah perspective - Muhamad Muizz Abdullah,; Abdul Bari Awang,; Mohamad Sabri Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
An illegitimate child is born outside of legal marriage by both parents, as a result of adultery. The implication is that their rights in the Islamic law are hindered, such as inheritance from their biological father. However, is it the child's right to be categorically denied from receiving his biological father's estate? What is the alternative in syarak, in caring for their welfare? This study will analyze the ruling of illegitimate child inheritance from a syariah perspective, and thus propose some solutions to the problem. This study applied a qualitative approach using the library research method. The findings were obtained from articles, cases from the Syariah Court, acts, enactments, and analysis of fatwas in Malaysia. To achieve this objective, interviews were also conducted with a takaful consultant and an executive from the Amanah Raya Berhad (ARB). This study found that the instruments of hibah takaful, will, trust or testamentary trust can be implemented in Islamic estate planning to safeguard the welfare of an illegitimate child.